2015
DOI: 10.5455/njppp.2015.5.2002201531
|View full text |Cite
|
Sign up to set email alerts
|

Drug prescription pattern for bronchial asthma in a tertiary-care hospital in Eastern India

Abstract: Background: A wide range of medications are now available for the treatment of asthma, and selection of optimal treatment is essential. Aims and Objective: To evaluate the drug-prescribing trend of antiasthmatic drug in a tertiary-care hospital. Materials and Methods: The prescription data from 130 patients with asthmapatients were studied using a prescription auditing pro forma. Data were recorded from the patients attending the outpatient department of Hi-Tech Medical College and Hospital from February to Ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 2 publications
2
6
0
Order By: Relevance
“…This shows that most of the patients had received antibiotics without confirming infection, and this could possibly result in over or misuse of antibiotics that culminates into development of resistance. A similar notion that antibiotics might be used (irrationally) had also been reported by Prasad et al [42]. In connection with this, Darmon et al [43] conducted a cross-sectional study using database in primary care of France and Italy and found 37.1% and 42.2% of antibiotic prescription, respectively.…”
Section: Pattern Of Antiasthmatic Drugsupporting
confidence: 62%
“…This shows that most of the patients had received antibiotics without confirming infection, and this could possibly result in over or misuse of antibiotics that culminates into development of resistance. A similar notion that antibiotics might be used (irrationally) had also been reported by Prasad et al [42]. In connection with this, Darmon et al [43] conducted a cross-sectional study using database in primary care of France and Italy and found 37.1% and 42.2% of antibiotic prescription, respectively.…”
Section: Pattern Of Antiasthmatic Drugsupporting
confidence: 62%
“…In the present study, prescription of multiple antiasthmatic drugs was considerably high (66%) which suggests adherence to standard treatment guidelines 1 . These findings comply with other published studies such as Garje, et al 17 , Karki, et al 27 and Prasad, et al 28 . Among the children treated with multiple drug therapy, two drug combinations (46%) were prescribed the most.…”
Section: Discussionsupporting
confidence: 94%
“…This study also found that the patients were mainly prescribed inhalational dosage forms of anti-asthmatic drugs. The studies by Trivedi, et al 26 and Prasad, et al 28 were also in the same line. The acceptance of inhalation therapy among patients suggests awareness among patients as well as counselling by the treating physician.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Another study done by Thomas et al [14] reported that combination therapy with ICS-LABA therapy was prescribed for 7% of patients which was quite low as compared to this study. Monotherapy was given in 24.19% of patients which is slightly higher than the study done in Gorakhpur by Pandey et al [15] (19%) but is lower than in a study done by Prasad et al [16], in which all patients were prescribed with multiple drug therapy.…”
Section: Discussionmentioning
confidence: 62%